Czech Republic : Technical Note on Stress Testing the Banking Sector. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This technical note summarizes stress tests undertaken for the Czech banking system as part of the Financial Sector Assessment Program (FSAP) Update. The tests were tailored to capture the specificities of the Czech banking system, characterized by a high share of foreign-owned banks. The program addressed current market developments and medium-term structural trends. All banks were assessed against solvency, liquidity, and contagion risks. The solvency tests revealed that the Czech banking system is robust even against substantial shocks on a standalone basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet